The Strategies and Mechanisms of Immune Checkpoint Inhibitors for Brain Metastases in NSCLC - Li, Ji; Wang, Min; Xu, Shuhui; Li, Yuying; Li, Jiatong; Yu, Jinming; Zhu, Hui (Frontiers in Pharmacology, 2022)
Brain metastases are more and more common among patients with non-small cell lung cancer (NSCLC). TKI therapy could provide ideal outcomes for patients harboring epidermal growth factor receptor or ALK mutations. For wild-type patients, however, survival is poor because there are few effective treatments other than radiotherapy. Immune checkpoint inhibitors (ICIs) have changed the management of advanced NSCLC. However, the exclusion of patients with active brain metastasis (BM) from most ICI trials precludes the generalization of results. Accordingly, a variety of appropriate real-world studies and clinical trials are being developed to evaluate tumor response. Increasingly encouraging results have suggested that ICIs could be active in the central nervous system (CNS) in select patients with high PD-L1 expression and low CNS disease burden. With the extensive use of ICIs in NSCLC patients with BM, many important questions have emerged concerning issues such as the clinical response to a single ICI, use of ICIs combined with chemotherapy or radiation, the biological mechanism and appropriate sequencing of local and systemic therapy combinations, and safety and toxicity. The present review summarizes the advances in systemic ICIs for the treatment of NSCLC patients with BM, discusses factors associated with efficacy and toxicity, and explores future directions.